2016
DOI: 10.5993/ajhb.40.5.12
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Smokeless Tobacco Expectancies Questionnaire to Snus

Abstract: Objective Measures of consumer perceptions of emerging tobacco products are needed for understanding the potential for product adoption and use. The purpose of this research was to evaluate the applicability of the Smokeless Tobacco Expectancies questionnaire to snus, and examine its association with interest in using snus. Methods A web-based recruited 116 adolescents (14-17 years of age), 463 young adults (18-34 years of age), and 596 older adults (35-65 years of age) from a web-based opt-in panel. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Peers play a significant role in establishing perceptions of normative pressure (i.e., conforming to be accepted by a group) and fostering attitudes towards risk-taking behavior. The relation between peer use of other tobacco products and self-reported use of these products is wellestablished (Adkison et al, 2016;Barnett et al, 2009;Hoffman et al, 2007;Montes et al, 2019;Wilkinson et al, 2009). For instance, one of the most reliable correlates of adolescent smoking is the smoking status of the adolescent's friends (Hoffman et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Peers play a significant role in establishing perceptions of normative pressure (i.e., conforming to be accepted by a group) and fostering attitudes towards risk-taking behavior. The relation between peer use of other tobacco products and self-reported use of these products is wellestablished (Adkison et al, 2016;Barnett et al, 2009;Hoffman et al, 2007;Montes et al, 2019;Wilkinson et al, 2009). For instance, one of the most reliable correlates of adolescent smoking is the smoking status of the adolescent's friends (Hoffman et al, 2007).…”
mentioning
confidence: 99%
“…Fishbien and Ajzen (1975) specify that expectancies, or the belief that a behavior will result in a particular outcome, influence behavioral intentions. There is a well-established association between expectancies of use (e.g., better reputation with friends, perceived risk for developing cancer) and individual use in cigarettes, cigars, and smokeless tobacco products in adolescents and young adults (Adkison et al, 2016;Barnett et al, 2009;Hoffman et al, 2007;Montes et al, 2018;Wilkinson et al, 2009). For e-cigarettes, positive expectancies-e-cigarettes being perceived as "cool" and a healthier alternative to cigarettes-can be a strong predictor of continued use in young adults (McKelvey et al, 2018;Doran & Brikmanis, 2016).…”
mentioning
confidence: 99%
“…Table 1 presents the characteristics of the sample. Students were considered current smokers when they indicated that they had already smoked 100 cigarettes in their lifetime and had smoked at least one time in the past 30 days (Adkison et al, 2016;Riou França et al, 2009).…”
Section: Characteristics Of the Samplementioning
confidence: 99%
“…This limits the B-WISDM external validity to this specific population (Vajer et al, 2011), as a majority of student smokers are not daily smokers, but rather smoke on occasions and are thus considered as "light" smokers (Levinson et al, 2007;Moran et al, 2004;Thompson et al, 2007). While the original version of the WISDM was used with college student smokers (e.g., Piasecki et al, 2011), and the B-WISDM has already been used to study the characteristics of non-daily smokers (e.g., Scheuermann, Mburu, et al, 2015;Scheuermann, Nollen, et al, 2015) or tested in a nonclinical sample (Adkison et al, 2016), only the PDM and SDM scores were used, and neither the dimensionality nor the measurement invariance of B-WISDM according to the type of smoker (daily vs. non-daily) were pre-tested. Testing the psychometric qualities of B-WISDM with non-daily smokers is thus necessary to justify its relevance to this particular smoker population.…”
Section: Introductionmentioning
confidence: 99%